Characterization of magnetic field at distribution substations - Said I.; Hussain H.B.; Dave V. (2023)
Magnetic field spot measurements were done at four distribution substations, three of them were of exactly the same design and capacity, while the fourth has similar design and half the capacity. The data collected were compared with one another. Taking into account loading of the substation during measurement period, it was found that magnetic field distributions were similar, with high peaks at low voltage cable connections to transformers and low-voltage switchgears. Magnetic fields decayed rapidly with distance. Magnetic field longitudinal and transverse linear plots crossing the middle of the substations were also constructed and these were also found to be similar. Magnetic field parameter plots give information of magnetic field of which the general public may likely be exposed to. These were found to be lower than the limit recommended by the most standards.